Fungsi Hukum Pidana Dalam Penanggulangan Tindak Pidana Narkotika ( Studi Pada Kasus Pengadilan Negeri Medan) - Nurmalawaty Nurmalawaty (DE LEGA LATA: JURNAL ILMU HUKUM, 2018)
Narcotics crime in Indonesia is still something urgent and complex. From the disclosure of narcotics crime cases which increasingly have various patterns and distribution networks, narcotics abuse also increases significantly both in terms of quantity and quality. Law Number 35 of 2009 concerning Narcotics is a criminal law policy which regulates acts and criminal sanctions that can be imposed on the perpetrators. The many cases of narcotics crimes whose perpetrators were sentenced, did not affect the decrease in crime rates. Even what happens to narcotics prisoners who are undergoing prison sentences are still able to control the circulation of narcotics from prison. This research focuses on judicial study, to find out how the implementation of judicial policies in deciding cases of Narcotics Crimes in the Medan District Court. This type of research is normative juridical research in a judicial policy order with a descriptive approach. The application of criminal sanctions with imprisonment and fines for narcotics crimes have not yet reached the goal of criminal prosecution, this can be seen from the lightness of court decisions and the existence of criminal disparities from court decisions against narcotics offenders.